The Role of the Medan City Legal Aid Institute in Providing Pro Bono Legal Aid to the Community - Yedija Martua Nainggolan; Janpatar Simamora; Januari Sihotang (Law Development Journal, 2026)
This study examines the role of the Legal Aid Institute (LBH) in Medan in providing free legal services to low-income communities. This service aligns with Law Number 16 of 2011 concerning Legal Aid, which emphasizes the importance of access to justice for those who utilize these services. However, the lack of public understanding and information about LBH is a major obstacle. The approach used in this study is a normative juridical approach coupled with an empirical approach, which includes regulatory analysis and interviews with various stakeholders. The results of this study indicate that LBH in Medan plays a crucial role in supporting the community through both litigation and non- litigation processes. Some challenges faced include limited workforce, low public awareness, and inadequate government support. Therefore, collaboration between the government, the community, and LBH is crucial to improve the effectiveness of free services for communities in need.